Sejarah Penutup Kepala Perempuan Kerinci (Kulok) - Raudathul Putri, Renia Renia (Universitas Negeri Semarang, 2023)
This article discusses the history of Kerinci women's head coverings (kulok). Kulok has been around since ancient times. Kulok is the traditional clothing of the Kerinci people which is part of Kerinci culture. The research method used is historical in nature because it involves effectively collecting historical sources, evaluating them critically, and presenting a written synthesis of the findings. Based on research results, kulok has become a separate identity for women in Kerinci. According to history, kulok has been around since the 7th century and at that time was used by Malay women to go to the rice fields by covering their heads with cloth to protect their heads from the weather conditions in Kerinci. Kulok is also used as a headrest to avoid the burden of carrying luggage on the head or as a head protector from the hot sun when Malay women go to work in the fields or berumo at that time. For women who wear the hijab, wearing the hijab first involves wearing a headscarf to cover the hair, ears and neck. Then put the nape on top of the head. Changes also occur in the materials used in the components in the kulok.